Guided waves in a composite winglet structure: Numerical and experimental investigations. (15th February 2019) - De Luca, A.; Perfetto, D.; De Fenza, A.; Petrone, G.; Caputo, F.
Abstract: The paper deals with numerical and experimental investigations aimed to develop a Finite Element (FE) model for predicting wave propagation in a blended composite winglet. Material anisotropy, inhomogeneity, multi-layered configuration and complex geometries tend to increase the complexity of the wave propagation phenomena and consequently the development of established FE models. Moreover, even if 2D finite elements seem to be not appropriate for modelling guided waves propagation, especially for complex anisotropic structural components, they are more attractive than 3D ones, because of the computational cost saving. For this reason, part of the presented research activity is addressed to investigate the efficiency of shell finite elements in modelling guided waves propagation in a such complex structure as a winglet. The development of an efficient model depends also on the numerical characterization of the medium within which guided waves propagate through. As a consequence, preliminary simple experimental bending and modal tests have been carried out to support the material properties modelling. Subsequently, guided wave propagation FE analyses were performed and the results compared with provided experimental data. A good agreement between numerical and experimental results of the different analyses has been achieved in terms of both signal time of flight and amplitudes.